ANALISIS DAYA TAHAN AEROBIK DAN ANAEROBIK PADA ATLET PUTRA DI UNIT KEGIATAN MAHASISWA BOLABASKET UNIVERSITAS NEGERI SURABAYA - IRDYAHNINGTYAS, NURUL; WISMANADI, HIMAWAN (Jurnal Kesehatan Olahraga, 2019)
Destinations of the study is to examine the results of the analysis of aerobic and anaerobic endurance in athletes men in the unit activity student basketball University State Surabaya. The study used a descriptive study quantitative methods survey to test and measurement. The study was carried out at the Field of Military Training at the Faculty of Sports Sciences, University of, Surabaya. The sample in the study amounted to 15 male athletes in the basketball student activity unit of the Surabaya State University. Management of data analysis for aerobic endurance is the MFT (Multistage Fitness Testtest) with data mean obtained 41.59 ml/kg/sec and standard deviation 6.33. For anaerobic endurance analysis is RAST (Running Anaerobic Sprint Test) with thedata mean obtained 12.21 and standard deviation 5.64. Results from this study showed that aerobic endurance in athletes men in the unit activities basketball student University State Surabaya mostly male athlete entered in both categories is as much as 46.67% and for anaerobic athletes sons in the unit activities basketball students at the University of Negeri Surabaya are most in the less category, namely as much as 60%. Keywords: Aerobic, Anarobic, Bolabasket.